mRNA levels of peroxisome proliferator-activated receptors and their coactivators are affected by glucose deprivation and oleate in human hepatoma hepG2 cells - Bogdanová, Kateřina; Uherková, Lenka; Poczatková, Hana; Rypka, Miroslav; Veselý, Jaroslav (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2007)
AIMS: Very modest changes in mRNA stability can affect critical points in cellular energy pathways. The aim of this study was to investigate the impact of energy abundant substrates on peroxisome proliferator-activated receptors (PPARs) and PPAR-gamma coactivators (PGCs) mRNA's steady-state levels. METHODS: Quantitative RT-PCR study was performed to assess the effect of zero or normal (5 mmol/l) glucose and/or oleic acid (0.3 mmol/l) on mRNA levels of (PPARs) (PGCs) in HepG2 cells. RESULTS: PGC-1alpha mRNA was significantly upregulated in glucose deprived cells (123 % of the control level; p < 0.05), while PGC-1beta mRNA was significantly enhanced in oleate-fed cells (134 % and 160 % of control levels for zero glucose plus oleate and normal glucose plus oleate, respectively; p < 0.05) during the 0.5 h incubation. Upon the 4 h incubation, PPAR-gamma1 and PGC-1alpha mRNAs were significantly elevated in cells lacking glucose (142 % and 163 % of control levels, respectively; p < 0.05). Oleate significantly suppressed PPAR-alpha and PGC-1beta mRNA levels in glucose-deprived cells (58 % and 49 % of control levels, respectively; p < 0.05). PPAR-gamma1 and -gamma2 mRNAs were significantly superinduced when the cells were treated with cycloheximide, whereas PPAR-alpha and PGC-1alpha and-1beta mRNAs were destabilized. Upon actinomycin D treatment, glucose shortage significantly stabilized PPAR-alpha mRNA, while PGC-1alpha mRNA was destabilized by oleate in glucose-deprived cells. CONCLUSIONS: Our findings provide evidence that transcriptional processes that are under the control of energetic substrates are interconnected with concurrent translational processes that can change stability of mRNAs.
Keywords: Cycloheximide; daktinomycin; Cell Line, Tumor; Up-Regulation; In Vitro Techniques; receptory aktivované proliferátory peroxizomů; PPAR gama; Protein Synthesis Inhibitors; techniky in vitro; lidé; Oleic Acid; nádory jater; kyselina olejová; upregulace; Dactinomycin; messenger RNA; polymerázová řetězová reakce s reverzní transkripcí; inhibitory syntézy proteinů; RNA, Messenger; cykloheximid; Liver Neoplasms; Reverse Transcriptase Polymerase Chain Reaction; glukosa; Glucose; Peroxisome Proliferator-Activated Receptors; PPAR gamma; nádorové buněčné linie; Humans